Education Reform Model at Faculty of Mechanical Engineering, Universiti Malaysia Pahang - M. M., Noor; K., Kadirgama; M. M., Rahman; M. R. M., Rejab; R. A., Bakar; Abdullah, Ibrahim (2000)

(untitled)
This paper presents the implementation of education reform model namely outcome-based education (OBE) in terms of course delivery, assessment, evaluation and continuous quality improvement (CQI) at the Faculty of Mechanical Engineering, Universiti Malaysia Pahang (UMP). It was formalized based on the quality management system principle which is formulated its philosophy on OBE as well as on teaching and learning to facilitate the implementation. Board of External Examiner (BEE), Board of Industry Advisor (BIA) and Board of Stakeholders (BOS) are engaged for the third party review on the faculty vision, mission, curriculum, and assessment. The aspects of delivery, assessment and evaluation are discussed.